Simultaneously genetic selection of wheat yield and grain protein quality in rice–wheat and soybean–wheat cropping systems through critical nitrogen efficiency-related traits - Chen, Yufeng; Wang, Kun; Chen, Haolan; Yang, Hongkun; Zheng, Ting; Huang, Xiulan; Fan, Gaoqiong (Frontiers in Plant Science, 2022)
Analyzing the contribution of nitrogen (N) uptake and utilization to grain yield and protein quality-related traits in rice-wheat (RW) and soybean-wheat (SW) cropping systems is essential for simultaneous improvements in the two target traits. A field experiment with nine wheat genotypes was conducted in 2018-19 and 2019-20 cropping years to investigate N uptake and utilization related traits associated with high wheat yield and good protein quality. Results showed that N uptake efficiency (NUpE) in RW cropping system and N utilization efficiency (NUtE) in SW cropping system explained 77.6% and 65.2% of yield variation, respectively, due to the contribution of fertile spikes and grain number per spike to grain yield varied depending on soil water and N availability in the two rotation systems. Lower grain protein content in RW cropping system in comparison to SW cropping system was mainly related to lower individual N accumulation at maturity, resulted from higher fertile spikes, rather than N harvest index (NHI). However, NHI in SW cropping system accounted for greater variation in grain protein content. Both gluten index and post anthesis N uptake were mainly affected by genotype, and low gluten index caused by high post anthesis N uptake may be related to the simultaneous increase in kernel weight. N remobilization process associated with gluten quality was driven by increased sink N demand resulted from high grain number per unit area in RW cropping system; while confined by low sink N demand and source capability resulted from low grain number per spike and water deficit limiting photosynthesis of flag leaf in SW cropping system. CY-25 obtained high yield and wet gluten content at the expense of gluten index in the two wheat cropping systems, due to low plant height and high post anthesis N uptake and kernel weight. From these results, we concluded that plant height, kernel weight and post anthesis N uptake were the critically agronomic and NUE-related traits for simultaneous selection of grain yield and protein quality. Our research results provided useful guidelines for improving both grain yield and protein quality by identifying desirable N-efficient genotypes in the two rotation systems.